Associations and Dissociations between Oculomotor Readiness and Covert Attention - Casteau, Soazig (Vision (Basel), 2019)
The idea that covert mental processes such as spatial attention are fundamentally dependent on systems that control overt movements of the eyes has had a profound influence on theoretical models of spatial attention. However, theories such as Klein’s Oculomotor Readiness Hypothesis (OMRH) and Rizzolatti’s Premotor Theory have not gone unchallenged. We previously argued that although OMRH/Premotor theory is inadequate to explain pre-saccadic attention and endogenous covert orienting, it may still be tenable as a theory of exogenous covert orienting. In this article we briefly reiterate the key lines of argument for and against OMRH/Premotor theory, then evaluate the Oculomotor Readiness account of Exogenous Orienting (OREO) with respect to more recent empirical data. These studies broadly confirm the importance of oculomotor preparation for covert, exogenous attention. We explain this relationship in terms of reciprocal links between parietal ‘priority maps’ and the midbrain oculomotor centres that translate priority-related activation into potential saccade endpoints. We conclude that the OMRH/Premotor theory hypothesis is false for covert, endogenous orienting but remains tenable as an explanation for covert, exogenous orienting.